Exploring the Impact of Virtual Classes on Second Language Interaction among Pre-Service Teachers - Jezzabelle F. de Leon (Researchparks Publishing, 2022)
The pandemic's transition to online learning modes forced numerous institutions to adjust to the changes it brought. The classroom environment was also altered, which affected discussion interaction. While interaction is a significant component in English language teaching and learning, given that language basically influences learning. Therefore, the aim of the study is to examine the effectiveness of virtual classes in second language interaction among pre-service teachers. The questionnaire that was employed in this research was from the study by Nesreen and Budoor (2020) on the impact of virtual classes on second language interaction. The data collected came from the pre-service teachers that are currently having online classes. Furthermore, the study analyzed if there is significant difference in the effectivity of virtual classes in promoting second language interaction across gender. The findings stated that the effectiveness of virtual classes on interaction is characterized as